Interleukin-19 in Breast Cancer. (22nd April 2013) - Chen, Ying-Yin; Li, Chien-Feng; Yeh, Ching-Hua; Chang, Ming-Shi; Hsing, Chung-Hsi
Abstract : Inflammatory cytokines within the tumor microenvironment are linked to progression in breast cancer. Interleukin- (IL-) 19, part of the IL-10 family, contributes to a range of diseases and disorders, such as asthma, endotoxic shock, uremia, psoriasis, and rheumatoid arthritis. IL-19 is expressed in several types of tumor cells, especially in squamous cell carcinoma of the skin, tongue, esophagus, and lung and invasive duct carcinoma of the breast. In breast cancer, IL-19 expression is correlated with increased mitotic figures, advanced tumor stage, higher metastasis, and poor survival. The mechanisms of IL-19 in breast cancer have recently been explored both in vitro and in vivo . IL-19 has an autocrine effect in breast cancer cells. It directly promotes proliferation and migration and indirectly provides a microenvironment for tumor progression, which suggests that IL-19 is a prognostic marker in breast cancer and that antagonizing IL-19 may have therapeutic potential.